The Fairy Tale and Its Uses in Contemporary New Media and Popular Culture Introduction - Claudia Schwabe (Humanities, 2016)
Ever since the beginning of the 21st century, the fairy tale has not only become a staple of the small and silver screen around the globe, it has also migrated into new media, overwhelming audiences with imaginative and spectacular retellings along the way. Indeed, modern fairy-tale adaptations pervading contemporary popular culture drastically subvert, shatter, and alter the public’s understanding of the classic fairy tale. Because of the phenomenally increasing proliferation of fairy-tale transformations in today’s “old” and “new” media, we must reflect upon the significance of the fairy tale for society and its social uses in a nuanced fashion. How, why, and for whom have fairy-tale narratives, characters, and motifs metamorphosed in recent decades? What significant intermedial and intertextual relationships exist nowadays in connection with the fairy tale? This special issue features 11 illuminating articles of 13 scholars in the fields of folklore and fairy-tale studies tackling these and other relevant questions.